Investigations into human tracheal cartilage osseocalcineus metaplasia II. Histopathological examination of tracheal cartilages - Sośnik, Henryk; Sośnik, Katarzyna (Polish Journal of Pathology, 2009)
Different opinions in the literature about changes in tracheal cartilages were the basis for investigations concerning the types of morphological changes occurring in ageing tracheal cartilages. 5 micron thick specimens stained with haematoxylin-eosin and in selected cases using von Kossa method of 371 cartilages taken from 95 male (mean age 56.6 ±13.4 years) and 279 cartilages from 70 female patients (mean age 64.9 ±16 years) (p < 0.001) were the investigated material. The analysis demonstrated statistically significant cartilage type differences between men and women (p < 0.001). Chondrolysis and asbestoids were observed in 11.9% of male and 2.9% of female patients. Calcium deposits were seen in 13.2% of male and 9.7% of female patients, while cartilage ossification in 20.5% and 3.6%, respectively. The coexistence of calcium deposits and osseous metaplasia was observed in 8.6% of male and 3.9% of female patients.